2013
DOI: 10.1016/j.foodqual.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Do polymorphisms in chemosensory genes matter for human ingestive behavior?

Abstract: In the last decade, basic research in chemoreceptor genetics and neurobiology have revolutionized our understanding of individual differences in chemosensation. From an evolutionary perspective, chemosensory variations appear to have arisen in response to different living environments, generally in the avoidance of toxins and to better detect vital food sources. Today, it is often assumed that these differences may drive variable food preferences and choices, with downstream effects on health and wellness. A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 142 publications
(196 reference statements)
5
90
1
2
Order By: Relevance
“…Previous reports have shown that the response to PROP was associated with increased bitterness and therefore reduced the liking for such vegetables as Brassicaceae (cruciferous) (27,32,47). The present participants, however, despite the apparent negative correlation for Brassicaceae vegetables, reported that the perceived PROP bitterness was not negatively correlated with the total vegetable intake (Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous reports have shown that the response to PROP was associated with increased bitterness and therefore reduced the liking for such vegetables as Brassicaceae (cruciferous) (27,32,47). The present participants, however, despite the apparent negative correlation for Brassicaceae vegetables, reported that the perceived PROP bitterness was not negatively correlated with the total vegetable intake (Tables 1 and 2).…”
Section: Discussioncontrasting
confidence: 67%
“…Such individual difference in the PTC/PROP taste status or TAS2R38 variation has been demonstrated to result in differences in the liking for some vegetables, fatty foods, spicy foods and alcoholic beverages (27,31,32). Previous studies have reported that PTC/PROPtasters had a lower consumption of glucosinolate-containing vegetables than non-tasters (27).…”
mentioning
confidence: 99%
“…Regarding gender, three articles reported that women are more sensitive to bitter taste also during pregnancy [22,23,43], and one did not find differences between genders regarding the number of gustatory papillae [50]. Different genetic expression, mainly of TAS2R38 and changes in the sensitivity to bitterness sensitivity, have been reported, influencing eating behavior and food preference, including alcohol ingestion [52,53,62]. Ethnic or cultural differences should always be considered because they appear to be crucial factors for food preference, justifying the discrepant results observed in the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…These early studies paved the way for nearly a century of research to understand the inheritance, molecular genetics, dietary implications, and evolutionary significance of this genetic variant. It is the most commonly researched genetic variation in chemosensation, but it is by far not the only example (67).…”
Section: Discovery Of Taste Variation In Bitter Thiourea Compoundsmentioning
confidence: 99%
“…TAS2R38 and PROP status are well studied, but numerous other polymorphisms impact taste perception, with potential implications for dietary intake (67). Additional studies are needed to understand how these polymorphisms interact with TAS2R38 variation and the PROP phenotype to influence eating behaviors and chronic health.…”
Section: Conclusion and Directions For Future Studiesmentioning
confidence: 99%